Diagnóstico da comunidade fitoplanctônica de um reservatório no semiárido nordestino - Silva, Merivalda Doroteu da (2013)
In the semiarid region of Brazil, in addition to water deficit, another serious problem of water availability is limiting water quality due to eutrophication, resulting from the use and occupation of space in the vicinity of water bodies and contributions in the areas of the reservoirs. This study was conducted at Oros reservoir in the state of Ceará which is inserted in the Brazilian semiarid region. This research aimed to study the variability of phytoplankton community and the quality of surface water reservoir Orós, between the years 2008 to 2011, identifying the dynamics of the class with the highest frequency and the most abundant species of cyanobacteria existing in these waters and their potential health risk humana.Para answer this question were performed in the range 17 bimonthly collection campaigns in seven points of the tank the following limnological parameters (chlorophyll a, transparency, total phosphorus, nitrate, temperature and pH), totaling 714 samples (17 campaigns x 7 x 6 points parameters). Transparency measures, temperature, and pH was performed in the field, while the other samples for analysis were collected directly in water 30 cm deep, placed in vials previously washed and decontaminated (polyethylene and amber glass) and kept refrigerated in coolers to the site analysis. According to the results of chlorophyll concentrations increased over the four years of study, but are still in line with the standards of CONAMA, which allows up 30μg.L-1 to class 2. It is observed that the increase of the mean attribute with time, whereas the opposite happens for transparency. With respect to nutrients, phosphorus has gradually increased, with a slight decline in 2010, when there was less precipitation and consequently a low runoff, the same can be observed for the nitrate values. The average water temperature was between 28 ° C and 30 ° C, indicating that the Oros has warm waters, characteristics of semiarid regions. The values of pH may be noted that were always alkaline soil because this environment is rich in bicarbonate ions. The phytoplankton composition was composed by Chlorophyceae, Cyanophyceae, Bacillariophyceae, Euglenophyceae, xantophyceae and Zygnemaphyceae, especially with larger Chlorophyceae and Cyanophyceae species despite the smaller number of species quantities of individuals were always higher than the other groups of individuals. The frequency of the cyanobacteria group arrived between 50 and 60% of the samples collected. Were also carried out quantitative and qualitative analyzes of the cyanobacterial group, and this group was the one that prevailed during the study period and more worrying is that most of his subjects are potentially toxic. It was observed that the amounts of cells were always higher than the amounts stipulated by CONAMA Resolution N°. 357/2005. When there was the abundance of species of cyanobacteria could be observed that the species Aphanocapsa sp. was most abundant in the first three years, but was replaced in 2011 by Planktotrix agardhii, since both species are considered in the literature as potentially toxic. The diversity decreased over the years, inferring that this reservoir is in a state of eutrophication.